A low-power portable scanner for body-worn Wireless Resistive Analog Passive (WRAP) sensors for mHealth applications. (June 2021) - Zaman, Md Sabbir; Morshed, Bashir I.
Abstract: Collecting multiple physiological signals with an embedded computing device can be more effective with battery-less zero-power sensors. We have previously reported our battery less, body-worn sensors named "Wireless Resistive Analog Passive (WRAP) sensors". Here, we report design, prototyping and functional validation of a low-power, small and portable signal acquisition (scanner, revision 4) device for these sensors. The scanner couples with these sensors inductively by on-board printed spiral coils (PSC) that rely on impedance mismatch technique for physiological signal collection. The scanner was fully tested, characterized, and validated in lab, as well as through deployment to users' home. As a test case, we show results of the scanner measuring temperature from WRAP temperature sensors with relative error within 0.01% range. The scanner measurement can distinguish between temperature of 1 °F difference and it shows excellent linear dependence between actual and measured resistance ( R 2 = 0 . 998 ). The scanner consumes 45.54 mJ of energy per scanning burst, it weighs 110 grams and measures 5.9"X 2.9"X 0.25". This device has demonstrated the possibility of small, low-power portable scanner for zero-power WRAP sensors that shows promise for real-life data collection from our study participants in Memphis Smart and Connected Community (S&CC). Highlights: A noble complete architecture for scanning bio-signals from WRAP sensors. The relative error of measurement on temperature WRAP sensor is 0.01%. The measurement can distinguish between temperature of 1 °F difference. Excellent linear dependence between actual and measured resistance ( R 2 = 0.998). This scanner demonstrates 10% reduction in energy from our previous version.